Educational Application of the Internet by Basic Pupils in Effutu Municipal Assembly: The Guidance and Counselling Implications - Nyamekye, Francis; Anapey, Gideon M. (International Journal of Educational Technology and Learning, 2019)
The study sought to investigate educational application of the Internet by basic school pupils in Effutu Municipal Assembly: The guidance and counselling implications. This study examined the use of the Internet among basic school pupils in Effutu Municipal Assembly. A descriptive survey approach was used to select forty- five (45) basic school pupils for the study. Snowball sampling technique was adopted which aided in the data collection. The study used an independent-samples t-test and one-way ANOVA to test Hypothesis 1 and Hypotheses 2 (null hypotheses) respectively. The result of the study reveals that educational use of the Internet is not the foremost priority of the basic school pupils but rather entertainment. The study also found that, sex is a significant factor in predicting Internet use among basic school pupils. Further studies could be carried out using a depth- interview schedule to further explore, whether basic school teachers guide their pupils use of the Internet for academic reasons.